2006
DOI: 10.1021/ol060739z
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Carbene Insertion on Polysubstituted Dihydroaromatic Compounds

Abstract: [reaction: see text] The rhodium-catalyzed CH-insertion reaction of diazo ester derivatives into dihydroaromatic compounds was expanded to the application of various polysubstituted and functionalized 1,4-dienes generated from a cobalt-catalyzed Diels-Alder reaction. The highly regioselective CH-insertion process produces after DDQ oxidation polysubstituted, polyfunctionalized aromatic compounds in good overall yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Carbene has aroused more attention because it has some advantages, such as significant role in medicament synthesization and tensile annulet, and can speed up the reaction and make the reaction readily [1][2][3][4] . Herein, the reactions of carbene with mulriple bond and its cycloaddition reaction have been reported systemically [5][6][7] .…”
mentioning
confidence: 99%
“…Carbene has aroused more attention because it has some advantages, such as significant role in medicament synthesization and tensile annulet, and can speed up the reaction and make the reaction readily [1][2][3][4] . Herein, the reactions of carbene with mulriple bond and its cycloaddition reaction have been reported systemically [5][6][7] .…”
mentioning
confidence: 99%
“…Unfortunately, diazo esters such as ethyl diazo acetoacetate, ethyl 2-diazo-3-methyl-butyrate, ethyl 2-diazo-4-phenyl-but-3-enoate or ethyl 2-diazo-propionate failed to give CH-insertion and only ethyl 2-diazo-2-phenyl-acetate (4b) gave the desired CH-insertion products after DDQ oxidation. 5 As reported in Table 3, the yields with Cu(hfacac) 2 and Rh 2 (OAc) 4 were comparable, and 1 H NMR analysis showed that the regioselectivity of the copper-catalysed reactions were the same as for the corresponding Rh(II)-catalysed reaction. Only the nitrogen-and sulfur-functionalised dienes 7e and 7f failed to react with the copper catalyst, while for diene 7e the rhodium catalyst led to acceptable conversion.…”
Section: Methodsmentioning
confidence: 56%
“…3 A more economic process is therefore desirable to minimise the use of excess reagents. 5 Therefore, we performed a series of reactions on two different dihydroaromatic compounds 3a and 3b with two diazo ester derivatives 4a and 4b (Scheme 1) to optimise the reaction conditions. To determine the regiochemistry of the products a DDQ oxidation to 6 was performed directly after the CH-insertion reaction.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, less than 5% of the cyclopropane was observed, and 53-64% yield of the C-H insertion product 88 was isolated in 91-95% ee. Davies [67,86], Doyle [87], and Hilt [88,89] have developed systems for selective C-H insertion into 1,4-cyclohexadiene derivatives (Fig. 7).…”
Section: Insertion Into Doubly Allylic Sitesmentioning
confidence: 99%
“…The ultimate fate of the diene differed in each case; in the indatraline synthesis it was ultimately oxidized to a benzene ring with DDQ, and in the preparation of cetiedil it was reduced to a cyclohexane with H 2 and Pd/C. Hilt took a slightly different approach toward the functionalization of cyclohexadienes [88,89]. He reasoned that subsequent DDQ oxidation of the insertion products would provide facile access to substituted benzene derivatives 101 that would be difficult to obtain by traditional means (Scheme 21).…”
Section: Insertion Into Doubly Allylic Sitesmentioning
confidence: 99%